Shear behavior and acoustic emission characteristics of en-echelon joints under constant normal stiffness conditions. (October 2020) - Zhang, Yuanchao; Jiang, Yujing; Asahina, Daisuke; Wang, Zhi
Highlights: The direct shear tests of en-echelon joints were conducted under constant normal stiffness (CNS) conditions. The shear failure mechanism and shear strength characteristics of en-echelon joints were analyzed. The effect of joint angle and normal stiffness was revealed. The acoustic emission (AE) response of en-echelon joints during the shear was studied. Abstract: En-echelon joints widely exist in rock slopes and underground rock masses, which seriously threaten the stability of rock engineerings. Majority of earlier studies have focused on conventional continuous joint, while the shear behavior of en-echelon joints has rarely been studied, especially under constant normal stiffness conditions. Therefore, in this study, the direct shear tests of en-echelon joints were conducted under constant normal stiffness conditions. The effect of joint angle and normal stiffness on shear strength characteristics and acoustic emission behavior was analysed. The test results showed that the shearing process of en-echelon joints includes two stages, i.e., Stage I and Stage II. Three different shearing mechanisms can be observed. Stage I involves the generation of wing cracks and Brazilian-like splitting of blocks, while Stage II is dominated by slipping and dilation of through-going shear zones. Accordingly, three shear strength indexes were distinguished, i.e., SR1a, SR1b and SR2. These three strength indexes vary greatly with the joint angle and normal stiffness, and can be predicted using numerical or theoretical method. In addition, the acoustic emission response of en-echelon joints during the shear can be divided into three stages according to the evolution of cumulative hit, i.e., initial growth phase, accelerated growth phase and decelerated growth phase. The increasing normal stiffness tends to cause a more intense energy release in Stage I and a larger number of cumulative hit in Stage II. Furthermore, an analysis of b -value showed that the shear failure intensity of en-echelon joints is greater when the joint angle is positive, especially close to 60°.